Combination of Helical CT and Doppler Sonography in the Follow-up of Patients with Clinical N0 Stage Neck Disease and Oral Cancer - Eida, Sato; Sumi, Misa; Yonetsu, Koichi; Kimura, Yasuo; Nakamura, Takashi (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Correctly diagnosing metastatic nodes is important for the follow-up of patients with clinical N0 stage neck disease and oral cancer. A combination of helical CT and Doppler sonography may facilitate the accurate detection of lymph node metastasis in patients with clinical N0 stage neck disease.METHODS: A combination of contrast-enhanced helical CT and Doppler sonography was performed to monitor the necks of 58 patients with initial clinical N0 stage neck disease. Of these patients, 17 underwent surgery; nodal metastasis in the neck was histopathologically confirmed. A node was diagnosed as metastatic if it fulfilled the CT criteria for metastatic nodes (short-axis diameter equal to or greater than the cutoff points for each level of the neck or central nodal necrosis) and if, additionally, it did not exhibit sonographic features for nonmetastatic nodes (normal hilar echogenicity and hilar flows). The presence of metastasis was confirmed histopathologically.RESULTS: During the follow-up periods, metastatic nodes were histologically confirmed in 17 (29%) patients. Of 30 metastatic nodes from the 17 patients with metastatic nodes, 22 (73%) appeared within the first year and 28 (93%) within the first 2 years; 20 developed from nonmetastatic nodes, and 10 were newly detectable. The combined criteria were effective in revealing 26 (87%) nodes, yielding 87% sensitivity, 100% specificity, and 100% positive and 99% negative predictive values. The independent use of one of these techniques alone resulted in low (67%) or moderate (87%) positive predictive values for sonography and CT, respectively. Seven hundred forty-one (97%) of 761 nodes that were nonmetastatic at initial examination remained nonmetastatic (737 nodes) or had disappeared (four nodes). As a result, a combination of CT and sonography was effective in revealing all 17 cases of metastatic nodes.CONCLUSION: A combination of contrast-enhanced helical CT and Doppler sonography is useful for the follow-up study of clinical N0 stage neck disease.